Are S-Klotho’s Maximal concentrations dependent on Exercise Intensity and Time in young adult males? - Saghiv, Moran Sciamama; Ben-Sira, David; Goldhammer, Ehud; Sagiv, Michael (Journal of Cardiology and Cardiovascular Medicine, 2019)
The purpose of the present study was to define the period of time in which aerobic training does not increase further serum S-Klotho levels in untrained young adult males, and to examine the relation between plasma S-Klotho concentration and maximal oxygen uptake (VO2max). Methods: Sixty (60) untrained subjects (27.05±1.1 years) were divided into 2 groups, both exercised six months 4×wk-1 for the duration of 45 min×session. One group (LTI) exercised below the anaerobic threshold at 40-50% of VO2max, while the second group (HTI) worked above the anaerobic threshold at 65-70% of VO2max. Testing sessions were performed at 0, 2, 4, and 6 months. Blood samples were drawn after overnight fasting; S-Klotho was analyzed using an ELISA kit. Results: Following 2 and 4 months, significant (p≤0.05) increases were noted in the HTI group, at the fourth testing session, S-Klotho leveled off. In the LTI group, S-Klotho remained almost unchanged. Findings of the present study, support emerging evidence suggesting that a relation between plasma S-Klotho concentration and VO2max exists. Conclusion: Data suggest that increases in S-Klotho is tidally associated with VO2max levels. In addition, the S-Klotho increase levels-off following 4 months of aerobic training. Exercising below the anaerobic threshold does not increase VO2max and thus, does not increase S-Klotho.